Chloroquine inhibits Paracoccidioides brasiliensis survival within human monocytes by limiting the availability of intracellular iron - Dias-Melicio, Luciane Alarcão [UNESP]; Moreira, Ana Paula [UNESP]; Calvi, Sueli Aparecida [UNESP]; Soares, Ângela Maria Victoriano de Campos [UNESP] (Wiley, 2006)
The mechanisms used by Paracoccidioides brasiliensis (Pb 18) to survive into monocytes are not clear. Cellular iron metabolism is of critical importance to the growth of several intracellular pathogens, including P. brasiliensis, whose capacity to multiply in mononuclear phagocytes is dependent on the availability of intracellular iron. Chloroquine, by virtue of its basic properties, has been shown to prevent release of iron from holotransferrin by raising endocytic and lysosomal pH, and thereby interfering with normal iron metabolism. Then, in view of this, we have studied the effects of CHLOR on P. brasiliensis multiplication in human monocytes and its effect on the murine paracoccidioidomycosis. CHLOR induced human monocytes to kill P. brasiliensis. The effect of CHLOR was reversed by FeNTA, an iron compound that is soluble at neutral to alkaline pH, but not by holotransferrin, which releases iron only in an acidic environment. CHLOR treatment of Pb 18-infected BALB/c mice significantly reduced the viable fungi recovery from lungs, during three different periods of evaluation, in a dose-dependent manner. This study demonstrates that iron is of critical importance to the survival of P. brasiliensis yeasts within human monocytes and the CHLOR treatment in vitro induces Pb 18 yeast-killing by monocytes by restricting the availability of intracellular iron. Besides, the CHLOR treatment in vivo significantly reduces the number of organisms in the lungs of Pb-infected mice protecting them from several infections. Thus, CHLOR was effective in the treatment of murine paracoccidioidomycosis, suggesting the potential use of this drug in patients' treatment.
Keywords: Chloroquine; Iron; Monocyte; Paracoccidioides brasiliensis; chloroquine; holotransferrin; iron; iron derivative; transferrin; unclassified drug; acidity; alkalinity; animal experiment; animal model; animal tissue; cell killing; cell level; cell survival; cell viability; controlled study; dose response; drug effect; drug efficacy; drug mechanism; experimental infection; fungicidal activity; human; human cell; in vivo study; infection prevention; intracellular membrane; iron kinetics; lung infection; male; monocyte; mouse; nonhuman; normal human; South American blastomycosis; Fungi; Murinae; Mus